Mapping the Politics and Socio-Economics of Early Islamic Government: Historical Review of the Khulafa' Al-Rashidun Period - Muzaiyana (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This paper aims to (1) Know the political arena of Islamic power during the Khulafa' al-Rashidun period. (2) Describe the succession events of the leadership of the Islamic government during the Companions period. (3) Understand the political and socio-economic development of Islamic society in the early Islamic world. This research uses qualitative methods through literature study techniques. The results of data tracking were analyzed using historical methods and case study theory. The results of this study indicate (1) the political arena during the reign of Khulafa' al-Rashidun can be categorized into two parts. First, at the beginning of the reign of the khulafa' al-Rashidun, the companions carried out internal consolidation, strengthening the ummah even though it was colored by fighting against enemies for interests based on Islamic values. Second, during the second half of the government, disputes began to occur between fellow Muslims, which led to civil war. (2) The event of succession or replacement of the caliph system in the era of the khulafa' al-Rashidun went according to the mechanism agreed upon at that time, so the four caliphs had different appointment models. (3) The socio-economic conditions of the Islamic community at that time went up and down according to political conditions and stability. The results of this study are expected to be a positive correlation for Muslims in Indonesia to implement Islamic political values in the context of national life within the framework of the unitary state of the Republic of Indonesia.